Diversity of hemiptera (true bugs) at paddy field in Sri Menanti, Kuala Pilah, Negeri Sembilan / Wan Nurfarahain Meor Zamari - Meor Zamari, Wan Nurfarahain (2016)
A study on diversity of Hemiptera at paddy field site in Sri Menanti, Kuala Pilah, Negeri Sembilan has been conducted to record species composition of Hemiptera and also to determine the diversity of Hemiptera at the particular area. The trapping methods used at study site were sweeping net, direct collection, yellow pan trap, and light trap. There are 2 suborders under order Hemiptera which are Heteroptera and Auchenorrhyncha. 4 families of Hemiptera found at the paddy field site were Alydidae, Gerridae, Cicadellidae and Pentatomidae. There were 80 individuals from genus Leptocorisa, 17 individuals from genus Gerris, 6 individuals from genus Cicadella and 1 individual from genus Nezara. Alydidae have the most species in this paddy field in Sri Menanti. By using Shannon-Wiener Diversity Index, the diversity was recorded as H’=0.70. Meanwhile, for species evenness, Shannon Evenness Index was used and was calculated as E’=0.51. The Margalef Richness Index showed the richness and abundance of the species with R’=0.64.